Pentingnya Pengelolaan Keuangan Bagi UKM IKM Kartika Nusantara Indonesia Wilayah Bekasi - Ossi Ferli; Ahmad Adriansyah; Debora Evianti Lumban Tobing; Poppy Sandra Melly; Putri Metha Ulinka Bangun; Nisrina Septi Hisanah; Niky Amelia (LPMP Imperium, 2023)
Financial management is an activity that all business actors will carry out. Even so, many still need to understand financial management properly. Not a few business actors run a business only by instinct and experience. UKM IKM Kartika Nusantara Indonesia Bekasi region is a partner in this activity. The problem UKM Kartika Nusantara Indonesia faced in the Bekasi region is a need for more understanding of effective financial management and distinguishing between business and personal finance. This community service activity was carried out so that Kartika Nusantara Indonesia SME actors in the Bekasi area could understand the importance of financial management. This PKM activity provides material on financial management. The implementation of the activity was carried out using lecture and discussion methods. The results of this PKM activity have significantly positive results in the average pre-test percentage, which initially showed a figure of 58.7%, increasing significantly to 83.6% in the post-test average percentage. This activity has an outstanding impact and can help develop knowledge and application in managing business finances and minimizing financial-related risks so that they can run their business effectively.